Fundamentals of Malaysian taxation - Lee Teck Heang (Thomson, 2007)
This book is written with readers' interest in our minds from the first page to the end. It is designed to provide a comprehensive framework of reference for students of Diploma, Degree or professional courses and tax practitioners. It outlines clearly the fundamental principles of the Malaysian Taxation in the most user friendly manner. The book is structured into 14 chapters which cover the essential topics in the course syllabus adapted by local universities, colleges and professional bodies. The content is presented in a simple and straight forward manner without compromising the comprehensive coverage. The 2006 Budget and its relevant changes are assimilated into this book so that our readers will be equipped with up-to-date information. The hard hitting facts coupled with Q&A at the end of each chapter will maximize the ability of the readers in understanding the basic principles without being overwhelmed